KONTRIBUSI MAJELIS ULAMA INDONESIA PROVINSI JAWA TIMUR DALAM MENUMBUHKEMBANGKAN INDUSTRI HALAL - Ubaidillah, M Hasan; Ningtyas, Mega Ayu (As-Syifa: Journal of Islamic Studies and History, 2025)
The enactment of Law of the Republic of Indonesia Number 33 of 2014 concerning Halal Product Assurance, so that the submission of halal certification by producers is mandatory. The provisions regarding the obligation of halal certification for all products are stated in Article 4 which states that: "Products entering, circulating and traded in the territory of Indonesia must be halal certified". The enactment of this Law is 5 years from the time the Law is enacted. So, in 2019 is the time for the implementation of the regulation which results in all products, including food products, having to be halal certified. Therefore, this study aims to analyze the contribution of the Indonesian Ulema Council (MUI) of East Java Province in developing the halal industry through the role of the MUI Fatwa Commission during the period 2022-2024. In this context, this study explores how the two institutions influence the development of the halal industry in East Java, especially in terms of issuing halal fatwas, product certification, and empowerment and assistance to industry players, including Micro, Small and Medium Enterprises (MSMEs). The method used in this study is the Asset-Based Community Development (ABCD) approach. Data collected through literature and field studies, namely data sources obtained from interview research on the elite of the East Java MUI, community leaders and business actors. The results of the study indicate that the MUI Fatwa Commission has a strategic role in providing a legal basis and fatwa that serves as a guideline for the community and industry players in ensuring that their products are in accordance with Islamic law principles. On the other hand, LPPOM MUI functions as an institution that manages the halal certification process, provides education and training for business actors, and supervises products that have been halal certified.However, this study also identified a number of challenges faced in efforts to develop the halal industry in East Java, such as the limited number of trained halal auditors, the high cost of certification for SMEs, and the lack of public understanding regarding the importance of halal products. However, MUI's contribution to developing the halal industry in East Java has proven significant, both in improving the quality of halal products and in strengthening the competitiveness of local industries in national and international markets. The suggestion from this assistance is for the MUI of East Java Province to increase human resource capacity, simplify halal certification procedures for SMEs, and strengthen socialization programs to the community about the importance of choosing halal products. Thus, it is hoped that the halal industry in East Java can develop more rapidly and provide a positive impact on the regional economy and the welfare of the people.